2020
DOI: 10.1002/mawe.201900045
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rare earth cerium on the impact toughness, corrosion and wear resistance of CrNiMnMo alloyed lining steel

Abstract: The effects of the addition of rare earth cerium on the impact corrosion and wear resistance of CrNiMnMo alloyed lining steel were studied using metallurgical microscopy, scanning electron microscope, x‐ray powder diffraction, a hardness tester, an impact tester, and an impact corrosion abrasion tester. The properties of CrNiMnMo alloyed lining steel with the addition of cerium were compared with that of CrNiMnMo steel without the addition of cerium after being heat treated by same processes. The results show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…[24,25] Adding rare earth elements to steel can refine the grain size. [18] Herein, studying the influence of rare earth elements on the size and distribution of TiC particles, the size of the martensite lath, and wear resistance in high-titanium wear-resistant steel is essential.…”
Section: Doi: 101002/srin202300053mentioning
confidence: 99%
See 2 more Smart Citations
“…[24,25] Adding rare earth elements to steel can refine the grain size. [18] Herein, studying the influence of rare earth elements on the size and distribution of TiC particles, the size of the martensite lath, and wear resistance in high-titanium wear-resistant steel is essential.…”
Section: Doi: 101002/srin202300053mentioning
confidence: 99%
“…[13][14][15][16][17] The addition of trace amounts of rare earth elements to steel makes the inclusion finer and denser effectively, improving the toughness, plasticity, and wear resistance of steel. [18][19][20][21] For example, The effect of the addition of Ce on the morphology of Al 2 O 3 inclusions, when added to the steel, was studied in the literature. [13] During solidification, when cerium was added to the steel for 1 min, there were still small amounts of inclusions that were not completely modified, which consisted of an Al 2 O 3 core wrapped in a CeAlO 3 ring.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sun et al [ 21 ] concluded that optimum Ce concentration with its homogeneous distribution in the matrix is the most effective at retarding the formation of secondary phases and therefore preventing the degradation of mechanical properties. Ahn et al [ 22 ] found obvious increase in the impact energy of the duplex stainless steel and the brittle‐to‐ductile transition temperature slightly decreased by ≈10 °C with the addition of Ga. Du et al [ 23 ] found that the impact toughness of the CrNiMnMo steel lining board improved greatly with the addition of cerium and the impact toughness increased by 22% with the fracture mode of being ductile. Wang et al [ 24,25 ] indicated through thermodynamic calculations that the denaturation sequence of Ce inclusions was Al 2 O 3 → CeAlO 3 → Ce 2 O 3 + Ce 2 O 2 S → Ce 2 O 2 S. The study could provide theoretical guidance for inclusion‐controlling perspective under different deoxidation conditions of the RE‐containing steel.…”
Section: Introductionmentioning
confidence: 99%